Dual Mutation: The Save the Mutants Approach - Delamaro, Márcio Eduardo (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2004: Anais do III Simpósio Brasileiro de Qualidade de SoftwareDO - 10.5753/sbqs.2004.16196, 2004)
Mutation testing is a fault based testing criterion that has been widely used and studied. It has been shown an eective fault revealing criterion and its characteristics allow its use in a large range of entities like regular programs and behavioral specications of real time systems. To evaluate the adequacy of a test set T in the test of a program P, mutation testing uses a set of alternative implementations of P called mutants. The adequacy of T is assessed by its ability on demonstrate that the mutants produce dierent results of P. In this paper we present the idea of Dual Mutation Testing (DMT). DMT uses the same mutants as mutation testing but requires test cases that show that the mutants can produce the same results of P. In a case study we apply Dual Mutation Testing and compare it to traditional mutation testing.